The Aegean Sea and the Eastern Mediterranean in the Global and Regional Balance Based on the Axes of Geography, History, and International Law - Ak, Mahmut; Alkan, Haluk; Unver, Metin (Istanbul University Press, 2021)
We have regretfully observed for many years that the academic community in Tur key, except in some limited areas, has failed to provide the necessary contribution about the issues that Turkey has had to deal with on international level, because the debates have been confined to superficial, oversimplified, and outdated ideological points of view in daily politics. However, the fundamental theses, discussions, and prospective guidance of politics, law, economics, and international relations would be much more lasting and effective once they are shaped by the robust data and theses of the academic community in Turkey. We hope that the book The Aegean Sea and the Eastern Mediterranean in the Global and Regional Balance Based on the Axes of Geography, History, and Interna tional Law drawn up in cooperation between the Grand National Assembly of Turkey and Istanbul University can contribute to creating such a horizon and produce theses to this effect. No matter what topic of international relations one may address, it is impossible to understand and present it independently of other problems and topics. Therefore, we need to gain insight into all incidents and processes that affect and shape the Eastern Mediterranean, and within this framework put forward our projections on the future of Turkey, which is a common concern and asset for all of us. We currently observe manifestations of a biased perspective that is far from fair concerning the ongoing events in the Eastern Mediterranean. The initiatives of Turkey, seeking her rights arising from the international law and agreements since the very beginning through legitimate means and methods, have been encountered by some countries and so-called alliances, which disregard international law and agreements and consider all kinds of illegitimate actions as their rights. Undoubtedly, it is desirable to collaborate, make efforts, and negotiate with approaches in goodwill, respecting international law and agreements aiming at establishing peace as well as the rights, and laws of nations and states. However, it is impossible to take action before realizing and having others realize the following facts: Some countries, in the global order lacking justice established in the aftermath of the Second World War, had only rights and interests. Some others had only duties and responsibilities. This bizarre and unjust order lasted for years. However, the world has now changed and the parameters creating this unjust order have collapsed. We observe that it takes time for some countries to come to terms with this reality. Every state and nation, when it comes to the international order, shall have rights and interests as well as duties and responsibilities. Such a world where this just state of affairs prevails is not far away. This book offers a comprehensive perspective addressing the Eastern Mediterra nean issue within the context of not only history, law, and international relations but also geography, geopolitics, and biodiversity. I hope that the ideas, recommendations and outcomes offered in the book will pave the way for new perspectives to locate the Eastern Mediterranean in the blue shade of peace. I would like to thank Prof. Mahmut AK, the Rector of Istanbul University, for his leadership in the publication of the book as well as the academics contributing their articles. I am pleased and confident that this book will be appreciated by the readers as an invaluable source of scholarship on the Eastern Mediterranean.